TRASH TO TRANSFORMATION: ENVIRONMENTAL JUSTICE IN WASTED BY ANKUR BISEN - Alex, Minu (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Environmental justice asserts that all individuals have the right to be shielded from environmental harm and to live in a healthy, pollution-free environment. Exploring environmental justice uncovers the many facets of "environment" and "justice." Ankur Bisen’s Wasted: The Messy Story of Sanitation in India, A Manifesto for Change delves into waste management challenges within India’s socio-political landscape. Bisen highlights how caste-based biases have influenced sanitation practices, delaying the recognition of ecological responsibility as a collective social duty. This paper examines how power structures contribute to systemic indifference toward communities compelled to live in unsanitary conditions. It critiques society’s apathy and the system’s audacity, analyzing the politics of power that shapes public attitudes through a Foucauldian lens on power structures.